Christian Final Year College Student: Preparedness and Consciousness in Adopting Biblical Principles to Survive and Thrive in Exile During the One-Year NYSC Program - Gilbert N, Alaribe; Okwuosa, Lawrence; Uroko, Favour (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2024)
This research aims to investigate the level of awareness and readiness of final year Christian students in adopting a biblical-based exile lifestyle model. Two research questions and two hypotheses were proposed to guide this study. A descriptive survey research design was employed. The sampling technique used proportional multistage stratified random sampling method to obtain a sample size of 340 final year Christian students in State-owned colleges in Imo Province. The researcher-developed assessment scale titled